Potential links between human bloodstream infection by Salmonella enterica serovar Typhimurium and international transmission to Colombia. - Yan Li; Caisey V Pulford; Paula Díaz; Blanca M Perez-Sepulveda; Carolina Duarte; Alexander V Predeus; Magdalena Wiesner; Darren Heavens; Ross Low; Christian Schudoma; Angeline Montaño; Neil Hall; et al. (PLoS Neglected Tropical Diseases)
Salmonella enterica serovar Typhimurium is a prevalent food-borne pathogen that is usually associated with gastroenteritis infection. S. Typhimurium is also a major cause of bloodstream infections in sub-Saharan Africa, and is responsible for invasive non-typhoidal Salmonella (iNTS) disease. The pathogen also causes bloodstream infection in Colombia, but there has been a lack of information about the S. Typhimurium isolates that were responsible. Here, we investigated the genomic characteristics of 270 S. Typhimurium isolates from bloodstream infection patients in Colombia, collected between 1997 and 2017. We used whole-genome sequencing to analyse multidrug-resistant (MDR) profiles, plasmid distribution, and to define phylogenetic relationships. The study identified the distinct sequence types and phylogenetic clusters of S. Typhimurium prevalent in Colombia. The majority of isolates (90.8%) were ST19, which is distinct from the iNTS-associated S. Typhimurium in sub-Saharan Africa (ST313). The two prominent clusters of MDR S. Typhimurium were either DT104 or closely related to the LT2 reference strain. We used a phylogenetic approach to associate the Colombian clusters with global S. Typhimurium isolates from public databases. By putting the Colombian S. Typhimurium isolates in the context of the global spread of DT104, ST313 and LT2-related variants, we found that the Colombian clusters were introduced to the country via multiple independent events that were consistent with international transmission. We suggest that the acquisition of quinolone and chloramphenicol resistance by the Colombian S. Typhimurium isolates was driven by horizontal gene transfer. Three ST313 isolates that caused bloodstream infection in Colombia were identified. These ST313 isolates were related to the Malawian ST313 lineage 3 & UK ST313, and shared a similarly high invasiveness index. To our knowledge, this is the first report of ST313 in Colombia.